1994
DOI: 10.1111/j.1550-7408.1994.tb01490.x
|View full text |Cite
|
Sign up to set email alerts
|

The α‐ and β‐Tubulin Genes of Euplotes octocarinatus

Abstract: The alpha- and the beta-tubulin genes of the hypotrichous ciliate Euplotes octocarinatus were isolated from a size-selected macronuclear DNA library. The alpha-tubulin gene is located on a 1,587 bp macronuclear DNA molecule and the beta-tubulin gene on a 1,524 bp macronuclear DNA molecule. Sequencing revealed that all the cysteine residues of the two genes are encoded by the common cysteine codons UGU and UGC and none by an UGA codon. This is in contrast to the genes of E. octocarinatus sequenced so far, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Alignment of some protozoan and vertebrate amino acid sequences of the ␤-tubulin COOH-domain. The ␤-T1 and ␤-T3 sequences of E. focardii are aligned with the ␤-tubulin sequences of the ciliates E. octocarinatus [Liang et al, 1994], E. crassus [Harper and Jahn, 1989], Tetrahymena pyriformis [Barahona et al, 1988], which is fully identical to the ␤-tubulin sequence of T. thermophila [Gaertig et al, 1993], and Paramecium tetraurelia [Dupuis, 1992] and with the sequences of the vertebrate ␤-tubulin isotypes (classes III and IV) [Sullivan and Cleveland, 1986] that show the highest similarity with protozoan ␤-tubulin. The ␤-tubulin sequence of the Antarctic fish Notothenia coriiceps neglecta [Detrich and Parker, 1993] is also included, being the only other known tubulin sequence of a poikilotherm organism.…”
Section: Detection Of Tubulin Posttranslational Modificationsmentioning
confidence: 99%
“…Alignment of some protozoan and vertebrate amino acid sequences of the ␤-tubulin COOH-domain. The ␤-T1 and ␤-T3 sequences of E. focardii are aligned with the ␤-tubulin sequences of the ciliates E. octocarinatus [Liang et al, 1994], E. crassus [Harper and Jahn, 1989], Tetrahymena pyriformis [Barahona et al, 1988], which is fully identical to the ␤-tubulin sequence of T. thermophila [Gaertig et al, 1993], and Paramecium tetraurelia [Dupuis, 1992] and with the sequences of the vertebrate ␤-tubulin isotypes (classes III and IV) [Sullivan and Cleveland, 1986] that show the highest similarity with protozoan ␤-tubulin. The ␤-tubulin sequence of the Antarctic fish Notothenia coriiceps neglecta [Detrich and Parker, 1993] is also included, being the only other known tubulin sequence of a poikilotherm organism.…”
Section: Detection Of Tubulin Posttranslational Modificationsmentioning
confidence: 99%
“…The genetic apparatus of E .octocarinatus consists, like in other ciliates, of two types of nuclei: the transcriptionally quiescent micronucleus and the transcriptionally active macronucleus. 12) It has generally been confirmed that in Euplotes, UGA is translated as cysteine 13) or selenocysteine, 14) and using UAA and UAG as the termination codon. In addition, a number of genes from Euplotes have been identified that appear to require a +1 PRF to produce their protein products.…”
mentioning
confidence: 94%
“…Liang and Heckmann () reported the first characterization of a γ‐tubulin‐encoding gene in a ciliate, which differed in some important respects from the α‐ and β‐tubulin genes that they analyzed in the same organism (Liang et al. ). Working in collaboration with French researchers from Gif‐sur‐Yvette and Toulouse, they then demonstrated the localization of γ‐tubulin in basal bodies (Liang et al.…”
mentioning
confidence: 99%